2021
DOI: 10.21608/ejentas.2021.92770.1414
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of the Revised Arabic Language test for 4-8-year old children

Abstract: Background: Clinicians use standardized assessments extensively in clinical and research settings to assess children's language skills and provide information for diagnosis, service eligibility, and intervention decisions. Aims:The study aimed at standardization of the newly designed and formatted "Arabic Language Test (ALT)" for the age range 4-8 years. Patients and Methods: Piloting of the test was done on 60 children with normal language development (15 from each one-year age) from 4-8 years old. The sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Some studies, including those that were excluded from the review, disregarded this upper boundary of preschool children who stutter. For example, Rifaie et al [54] determined the age range between 4 and 7.5 years, Simonska [45] between 3.2 and 6.9 years, and Abou El-Ella et al [55] between 3 and 8 years. To understand clinical implications and draw strong conclusions, it is important to study a single population with standardized age ranges, especially when designing experimental studies.…”
Section: Age Categorizations For the Studies Conducted Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies, including those that were excluded from the review, disregarded this upper boundary of preschool children who stutter. For example, Rifaie et al [54] determined the age range between 4 and 7.5 years, Simonska [45] between 3.2 and 6.9 years, and Abou El-Ella et al [55] between 3 and 8 years. To understand clinical implications and draw strong conclusions, it is important to study a single population with standardized age ranges, especially when designing experimental studies.…”
Section: Age Categorizations For the Studies Conducted Inmentioning
confidence: 99%
“…Five studies were excluded from the review because the number of weekly clinical visits on which authors reported was limited to 12 [25,54,55], 16 [27], or 36 [57] for all participants in their research protocols. The participants of these studies did not reach stage 2 of the Lidcombe Program based on the data provided [15].…”
Section: Delivering the Lidcombe Program In A Limited Number Of Sessionsmentioning
confidence: 99%
“…It was one of the first studies to measure language proficiency in Arabic for foreign speakers. Consequently, research about the standardization of language proficiency examinations emerged and became the primary focus of Arabic linguists' research (Ben Khiroun et al, 2014;de Graaf, 2021;Masrai & Milton, 2019;Rifaie et al, 2021;Winke & Aquil, 2014).…”
Section: Introductionmentioning
confidence: 99%